Double-rare-earth-based composite catalyst as well as preparation method and application thereof
Perovskite-fluorite composite nanooxides were prepared by co-precipitation method of double rare earth-based composite catalysts, which solved the problem of low activity of transition metal oxide catalysts under high humidity conditions, and achieved efficient and stable ozone decomposition effect. It can control ozone pollution and reduce preparation costs.
Patent Information
- Application Number
- CN202411429451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-13
AI Technical Summary
Existing transition metal oxide catalysts are low in activity under high humidity conditions and are easily covered by intermediate products or water molecules, resulting in a decrease in catalyst activity and stability, making it difficult to design ozone decomposition catalytic materials with high catalytic activity and moisture resistance.
The perovskite structure and fluorite structure composite nanooxides were prepared by co-precipitation method using double rare earth composite catalysts, and nanostructures were formed by mixed alkalis of different alkalinity, which improved the redox capacity and moisture resistance of the catalyst and enhanced interface defects. The number of points and strong interactions are enhanced to improve the ozone decomposition effect of the catalyst under humidity conditions.
It achieves efficient and stable ozone decomposition performance under high humidity conditions in room temperature and is suitable for atmospheric ozone pollution control, and is simple in preparation and low in cost.
Smart Images

Figure CN119114048A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an ozone decomposition catalyst and a preparation method and application thereof, belonging to the technical field of gas purification and treatment in the environmental field. Background Art
[0002] Ozone mainly comes from the photochemical reaction of volatile organic compounds and nitrogen oxides. The increase in atmospheric oxidation caused by it and the synergistic effect with other pollutants in multiphase reactions are important causes of haze pollution in my country. In addition, long-term exposure to an environment with high ozone concentrations may cause permanent lung damage and other respiratory diseases. Therefore, the research and development of efficient O3 decomposition technology is of great significance to ecological environment governance and human health protection. At present, common O3 decomposition methods include: activated carbon adsorption method, plasma decomposition method, radiation decomposition method, liquid absorption method, catalytic decomposition method, etc. Among them, the ozone catalytic decomposition method can achieve efficient decomposition of ozone at room temperature, and at the same time does not produce any secondary pollution. It is currently the ozone removal technology with the most research value and application potential.
[0003] At present, transition metal oxides have attracted extensive attention in the field of catalysis due to their excellent stability, abundant reserves and easy preparation. x The article reports that a cerium precursor-doped manganese oxide catalyst was synthesized by a hydrothermal method, and it was found that the catalyst of ammonium cerium nitrate-doped manganese dioxide has good performance in decomposing ozone. xcatalysts[J].Clean Technologies and Environmental Policy,2024.DOI10.1007 / s10098-023-02725-7The article reports that nickel-doped manganese oxide catalysts with different degrees of defects were prepared by adjusting the ratio of precursors by hydrothermal synthesis. The influence of the molar ratio of precursors on the physicochemical properties and ozone removal effect of the catalyst under high humidity conditions was systematically studied. CN105289585A discloses a method for preparing a supported rare earth-doped manganese oxide for an ozone catalyst, which uses alumina as a carrier, manganese oxide as an active component of the catalyst, and rare earth elements as additives to prepare rare earth-doped MnO2-modified γ-Al2O3 with high catalytic decomposition of ozone. CN112473728A discloses an efficient and moisture-resistant ozone decomposition catalyst, its preparation method and application. The preparation method of the catalyst first uses a molecular sieve as a carrier, impregnates manganese oxide and copper oxide precursors, and dries and calcines to obtain a finished catalyst. This preparation method has low raw material cost and has high efficiency in removing high-concentration ozone. Although previous research reports have revealed the key role of transition metal oxide catalysts in the ozone decomposition process, their preparation process is complicated and the active sites are easily covered by intermediates or water molecules, resulting in decreased catalyst activity and stability. Therefore, designing ozone decomposition catalytic materials with high catalytic activity and high moisture resistance is still a huge challenge. Summary of the invention
[0004] Based on the problem of low activity under humidity conditions in the presence of current transition metal catalysts, the present invention provides a double rare earth-based composite catalyst and a preparation method and application thereof, wherein a composite nano-oxide with a perovskite structure and a fluorite structure is prepared by a co-precipitation method using a combination of multiple precipitants. The composite oxide has a high specific surface area and a porous structure, and a large number of active sites and interface defects are exposed on the surface. The catalyst has efficient ozone decomposition performance under high humidity conditions.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] Based on the current research status of ozone catalysis, the present invention provides a double rare earth-based composite catalyst and a preparation method and application. Using mixed alkalis of different basicities as composite precipitants, a composite precursor with a nanostructure is formed by coprecipitation method and the synergistic effect of hydroxide, carbonate and ammonium ions, and a double rare earth-based composite nano oxide is prepared by specific high-temperature heat treatment. The composite nano oxide is composed of a composite of a perovskite oxide and a fluorite oxide. The composite catalyst has a high content of oxygen vacancies and interface defect sites. The lanthanum-based and cerium-based perovskite oxides provide higher redox ability and catalytic stability, and the cerium-based fluorite oxide provides stronger surface oxygen vacancies and oxygen storage and release capacity. The number of interface defects of the two structures is adjusted and the strong interaction provides the catalyst with high moisture resistance, thereby improving the catalytic decomposition of ozone under humidity conditions.
[0007] A method for preparing a double rare earth composite oxide catalyst comprises the following steps: firstly, adding a precipitant solution into a solution containing a double rare earth metal salt and a transition metal salt, stirring the solution evenly, and then precipitating and aging the solution at room temperature for 6-24 hours; centrifuging, washing and drying the solution after aging to obtain a powdery precursor; and finally calcining the powdery precursor at 400-700°C for 2-6 hours to obtain the double rare earth composite oxide catalyst.
[0008] In the above preparation method: the double rare earth metals are lanthanum and cerium, and their salts are one of nitrate, chloride and acetate; the transition metal salt is one of manganese and cobalt, and its salt is one of nitrate and acetate.
[0009] In the above preparation method: the molar ratio of lanthanum, cerium and transition metal is 0.2-2:0.2-2:1;
[0010] In the above preparation method: the precipitant in step (2) is sodium hydroxide, ammonia water and sodium carbonate in a molar ratio of 0.1-3:0.1-1:1.
[0011] 10. In the above preparation method: the molar ratio of lanthanum, cerium, transition metal and composite precipitant is 0.2-2:0.2-2:1:7-10.
[0012] A double rare earth type composite oxide catalyst is prepared by the above method.
[0013] In the technical solution of the present invention: the catalyst is a composite oxide formed by a fluorite structure and a perovskite structure.
[0014] In the technical solution of the present invention, the double rare earth composite oxide catalyst prepared by the above method is used in ozone treatment.
[0015] Furthermore, the test conditions for the catalytic decomposition of ozone by the composite oxide are: the initial concentration of O3 is 50-100 ppm, the relative humidity is 50-90%, and the air velocity is 100000-120000 h -1 , the particle size of the catalyst is 40-60 mesh, the reaction temperature is room temperature, and the reaction time is 6 to 8 hours.
[0016] Beneficial effects:
[0017] The preparation method of the present invention is simple, low in cost and rich in raw materials; the prepared double rare earth-based composite oxide has a nano-scale structure, a high specific surface area and contains a large number of oxygen vacancies and interface defects on the surface. The double rare earth-based composite oxide catalyst exhibits high efficiency and stable catalytic decomposition of ozone under room temperature and humidity conditions, and is suitable for the treatment of ozone pollution in the atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 XRD pattern of the double rare earth based composite oxide catalyst prepared in Example 1.
[0019] Figure 2 The catalytic decomposition ozone performance of the catalysts prepared in Examples 1-4 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto:
[0021] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0022] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0023] Example 1
[0024] (1) 0.2 mmol of cerium nitrate, 1.8 mmol of lanthanum nitrate and 1 mmol of manganese acetate were added to 150 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 1, wherein the molar ratio of lanthanum, cerium and manganese was 0.2:1.8:1;
[0025] (2) 1.6 mmol of sodium hydroxide, 3.2 mmol of ammonia water (14 mol / L) and 4 mmol of sodium carbonate were added to 10 ml of water in sequence, stirred and dissolved to obtain a mixed solution 2, wherein the molar ratio of sodium hydroxide, ammonia and sodium carbonate was 0.4:0.8:1;
[0026] (3) slowly adding the mixed solution 2 of step (2) dropwise to the mixed solution 1 of step (1), stirring and mixing for 2 hours to obtain a mixed solution 3;
[0027] (4) subjecting the mixed solution 3 obtained in step (3) to precipitation aging at room temperature for 12 hours;
[0028] (5) Centrifuging, washing and drying the mixed solution after the reaction in step (4) to obtain a powdered precursor A; (6) calcining the powdered precursor A in step (5) at 500° C. for 6 hours to obtain a double rare earth composite oxide catalyst A.
[0029] (7) Testing the ozone removal performance of the double rare earth composite oxide catalyst A, initial O3 concentration (90 ppm); relative humidity (RH) of 50%; space velocity of 100000 h -1 The particle size is 40-60 mesh. After 8 hours of reaction at normal temperature and pressure, the ozone removal efficiency of the catalyst is 99%.
[0030] Example 2
[0031] (1) 1 mmol of cerium nitrate, 0.5 mmol of lanthanum nitrate and 1 mmol of cobalt acetate were added to 150 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 1, wherein the molar ratio of lanthanum, cerium and cobalt is 1:0.5:1;
[0032] (2) 0.8 mmol sodium hydroxide, 4 mmol ammonia water and 4 mmol sodium carbonate were added to 10 ml water in sequence, stirred and dissolved to obtain a mixed solution 2, wherein the molar ratio of sodium hydroxide, ammonia and sodium carbonate was 0.2:1:1;
[0033] (3) slowly adding the mixed solution 2 of step (2) dropwise to the mixed solution 1 of step (1), stirring and mixing for 3 hours to obtain a mixed solution 3;
[0034] (4) subjecting the mixed solution 3 obtained in step (3) to precipitation aging at room temperature for 8 hours;
[0035] (5) Centrifuging, washing and drying the mixed solution after the reaction in step (4) to obtain a powdered precursor B; (6) calcining the powdered precursor B in step (5) at 600° C. for 4 hours to obtain a double rare earth composite oxide catalyst B.
[0036] (7) Testing the ozone removal performance of the double rare earth composite oxide catalyst B, initial O3 concentration: 50 ppm; relative humidity (RH) 90%; space velocity 120000 h -1 The particle size is 40-60 mesh. After 8 hours of reaction at normal temperature and pressure, the ozone removal efficiency of the catalyst is 99%.
[0037] Example 3
[0038] (1) 1.8 mmol of cerium nitrate, 0.3 mmol of lanthanum nitrate and 1 mmol of manganese acetate were added to 150 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 1, wherein the molar ratio of lanthanum, cerium and manganese was 1.8:0.3:1;
[0039] (2) 5 mmol of sodium hydroxide, 0.4 mmol of aqueous ammonia and 2 mmol of sodium carbonate were added to 10 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 2, wherein the molar ratio of sodium hydroxide, ammonia and sodium carbonate was 2.5:0.2:1;
[0040] (3) slowly adding the mixed solution 2 of step (2) dropwise to the mixed solution 1 of step (1), stirring and mixing for 3 hours to obtain a mixed solution 3;
[0041] (4) subjecting the mixed solution 3 obtained in step (3) to precipitation aging at room temperature for 16 hours;
[0042] (5) Centrifuging, washing and drying the mixed solution after the reaction in step (4) to obtain a powdered precursor C; (6) calcining the powdered precursor C in step (5) at 650° C. for 2 hours to obtain a double rare earth composite oxide catalyst C.
[0043] (7) Testing the ozone removal performance of the double rare earth composite oxide catalyst C, initial O3 concentration: 60 ppm; relative humidity (RH) 50%; space velocity 100000 h -1 The particle size is 40-60 mesh. After 8 hours of reaction at normal temperature and pressure, the ozone removal efficiency of the catalyst is 100%.
[0044] Example 4
[0045] (1) 0.8 mmol of cerium nitrate, 1.2 mmol of lanthanum nitrate and 1 mmol of cobalt acetate were added to 150 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 1, wherein the molar ratio of lanthanum, cerium and cobalt was 0.8:1.2:1;
[0046] (2) 4 mmol of sodium hydroxide, 1.6 mmol of aqueous ammonia and 4 mmol of sodium carbonate were added to 10 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 2, wherein the molar ratio of sodium hydroxide, ammonia and sodium carbonate was 1:0.4:1;
[0047] (3) slowly adding the mixed solution 2 of step (2) dropwise to the mixed solution 1 of step (1), stirring and mixing for 5 hours to obtain a mixed solution 3;
[0048] (4) subjecting the mixed solution 3 obtained in step (3) to precipitation aging at room temperature for 24 hours;
[0049] (5) The mixed solution after the reaction in step (4) is centrifuged, washed and dried to obtain a powdered precursor D; (6) The powdered precursor D in step (5) is calcined at 450° C. for 5 hours to obtain a double rare earth composite oxide catalyst D.
[0050] (7) Testing the ozone removal performance of the double rare earth composite oxide catalyst D, initial O3 concentration: 100 ppm; relative humidity (RH) 60%; space velocity 100000 h -1 The particle size is 40-60 mesh. After 8 hours of reaction at normal temperature and pressure, the ozone removal efficiency of the catalyst is 99%.
[0051] Comparative Example 1
[0052] (1) 0.2 mmol of cerium nitrate, 1.8 mmol of lanthanum nitrate and 1 mmol of manganese acetate were added to 150 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 1;
[0053] (2) Add 8.8 mmol of sodium hydroxide to 10 ml of water and stir to dissolve to obtain a mixed solution 2;
[0054] (3) slowly adding the mixed solution 2 of step (2) dropwise to the mixed solution 1 of step (1), stirring and mixing for 2 hours to obtain a mixed solution 3;
[0055] (4) subjecting the mixed solution 3 obtained in step (3) to precipitation aging at room temperature for 12 hours;
[0056] (5) The mixed solution after the reaction in step (4) is centrifuged, washed and dried to obtain a powdery precursor E; (6) The powdery precursor E in step (5) is calcined at 500° C. for 6 hours to obtain a double rare earth composite oxide catalyst E.
[0057] (7) Testing the ozone removal performance of the double rare earth composite oxide catalyst E, initial O3 concentration (90 ppm); relative humidity (RH) of 50%; space velocity of 100000 h -1 The particle size is 40-60 mesh. After 8 hours of reaction at normal temperature and pressure, the ozone removal efficiency of the catalyst is 35%.
[0058] Comparative Example 2
[0059] (1) 0.2 mmol of cerium nitrate, 1.8 mmol of lanthanum nitrate and 1 mmol of manganese acetate were added to 150 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 1;
[0060] (2) Add 8.8 mmol of sodium carbonate into 10 ml of water and stir to dissolve to obtain a mixed solution 2;
[0061] (3) slowly adding the mixed solution 2 of step (2) dropwise to the mixed solution 1 of step (1), stirring and mixing for 2 hours to obtain a mixed solution 3;
[0062] (4) subjecting the mixed solution 3 obtained in step (3) to precipitation aging at room temperature for 12 hours;
[0063] (5) The mixed solution after the reaction in step (4) is centrifuged, washed and dried to obtain a powdered precursor F; (6) The powdered precursor F in step (5) is calcined at 500° C. for 6 hours to obtain a double rare earth composite oxide catalyst F.
[0064] (7) Testing the ozone removal performance of the double rare earth composite oxide catalyst F, initial O3 concentration (90 ppm); relative humidity (RH) of 50%; space velocity of 100000 h -1 The particle size is 40-60 mesh. After 8 hours of reaction at normal temperature and pressure, the ozone removal efficiency of the catalyst is 41%.
[0065] Comparative Example 3
[0066] (1) 0.2 mmol of cerium nitrate, 1.8 mmol of lanthanum nitrate and 1 mmol of manganese acetate were added to 150 ml of water in sequence, and stirred to dissolve to obtain a mixed solution 1;
[0067] (2) Add 8.8 mmol of aqueous ammonia to 10 ml of water and stir to dissolve to obtain a mixed solution 2;
[0068] (3) slowly adding the mixed solution 2 of step (2) dropwise to the mixed solution 1 of step (1), stirring and mixing for 2 hours to obtain a mixed solution 3;
[0069] (4) subjecting the mixed solution 3 obtained in step (3) to precipitation aging at room temperature for 12 hours;
[0070] (5) The mixed solution after the reaction in step (4) is centrifuged, washed and dried to obtain a powdered precursor G; (6) The powdered precursor G in step (5) is calcined at 500° C. for 6 hours to obtain a double rare earth composite oxide catalyst G.
[0071] (7) Testing the ozone removal performance of the double rare earth composite oxide catalyst G, initial O3 concentration (90 ppm); relative humidity (RH) of 50%; space velocity of 100000 h -1 The particle size is 40-60 mesh. After 8 hours of reaction at normal temperature and pressure, the ozone removal efficiency of the catalyst is 42%.
Claims
1. A method for preparing a double rare earth composite oxide catalyst, characterized in that: The method comprises the following steps: firstly adding a composite precipitant solution into a solution containing a double rare earth metal salt and a transition metal salt, stirring the solution evenly, and then precipitating and aging the solution at room temperature for 6-24 hours; After aging, the powder is centrifuged, washed and dried to obtain a powder precursor; finally, the powder precursor is calcined at 400-700° C. for 2-6 hours to obtain a double rare earth composite oxide catalyst.
2. The method according to claim 1, characterized in that: The double rare earth metals are lanthanum and cerium, and their salts are one of nitrate, chloride and acetate; the transition metal salt is one of manganese and cobalt, and its salt is one of nitrate and acetate.
3. The method according to claim 2, characterized in that: The molar ratio of lanthanum, cerium and transition metal is 0.2-2:0.2-2:
1.
4. The method according to claim 1, characterized in that: The composite precipitant in step (2) is sodium hydroxide, ammonia water and sodium carbonate in a molar ratio of 0.1-3:0.1-1:
1.
5. The method according to claim 1, characterized in that: The molar ratio of lanthanum to the composite precipitant is 0.2-2:7-10.
6. A double rare earth composite oxide catalyst, characterized in that: The catalyst is prepared by the method described in any one of claims 1 to 4.
7. The double rare earth composite oxide catalyst according to claim 5, characterized in that: The catalyst is a composite oxide formed by a fluorite structure and a perovskite structure.
8. Use of the double rare earth composite oxide catalyst prepared by the method of claim 1 in ozone treatment.
9. The use according to claim 7, wherein the composite oxide catalytic decomposition of ozone test conditions: initial concentration of O3 is 50-100ppm, relative humidity is: 50-90%, space velocity is: 100000-120000h -1 , the particle size of the catalyst is 40-60 mesh, the reaction temperature is room temperature, and the reaction time is 6 to 8 hours.
